2017
DOI: 10.21037/hbsn.2016.12.05
|View full text |Cite
|
Sign up to set email alerts
|

Setting up a robotic hepatectomy program: a Western-European experience and perspective

Abstract: Currently the majority of liver resections are performed via open resection. Nevertheless, minimally invasive liver surgery is gaining ground and conventional laparoscopy has proven to be beneficial in different fields of liver surgery compared to open resections. Still, conventional laparoscopy has a few downsides, from which straight instruments, 2-dimensional view and awkward ergonomics are the most obvious. The robotic surgical system is developed to overcome these limitations. It offers several advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Contrary to robotic liver resections, reports on robotic deroofing of liver cysts are extremely limited. 22,23 In our experience, robotic deroofing has been shown to be safe and feasible for various cyst locations, and to our knowledge, this is the largest reported series to date.…”
Section: Discussionmentioning
confidence: 72%
“…Contrary to robotic liver resections, reports on robotic deroofing of liver cysts are extremely limited. 22,23 In our experience, robotic deroofing has been shown to be safe and feasible for various cyst locations, and to our knowledge, this is the largest reported series to date.…”
Section: Discussionmentioning
confidence: 72%
“…It was applied for liver surgery in early 2010s, the initial experiences showed that robotic system can be used not only minor but also major liver resection (109,110). Recent reviews summarized the half-decade development of robotic liver surgery (111,112). Not limited to similar efficiency compared to conventional laparoscopic approach, its unique advantages of facilitating suturing under laparoscope allow it to provide more possibilities in the future.…”
Section: Robot Hepatectomymentioning
confidence: 99%
“…In fact, some papers showed that parenchymal-sparing resection of the postero-superior segments was performed more often by a robotic approach in comparison with laparoscopic procedures, which commonly extend to a major resection (11). An additional advantage is less surgeon fatigue, especially in longer procedures (5).…”
Section: Editorialmentioning
confidence: 99%
“…Therefore, the worldwide rise of audited national registers, national survey inquiries (6) and coordinated multi-center programs (3,5) on the appropriateness of MILR and the diffusion of robotic liver resection, especially given the difficulty in establishing randomized controlled trials, is highly desirable.…”
Section: Editorialmentioning
confidence: 99%